Glass-ceramic, tempered glass, preparation method thereof, housing of electronic device, display screen of electronic device and electronic device
By microcrystallizing and chemically strengthening the glass, nanocrystalline particles and compressive stress layers are formed, which solves the problem of poor drop resistance of glass, significantly improves drop resistance and fracture toughness, and is suitable for shells and display screens of electronic equipment. .
Patent Information
- Application Number
- CN202210058886.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-01-17
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2042-01-17
AI Technical Summary
As the shell or display screen of electronic equipment, glass has poor resistance to drop resistance and is difficult to meet the demand for drop resistance and drop resistance.
By microcrystallation and chemical strengthening of the parent glass, nanocrystalline particles and compressive stress layers are formed, which improves the fracture toughness and drop resistance of the glass.
The fracture toughness and drop resistance of the glass are significantly improved, the ball drop height increases by more than 30%, and the fracture toughness increases by more than 20%, while maintaining high light transmittance and transparency, which is suitable for the shells and display screens of electronic equipment.
Smart Images

Figure CN116477843B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of electronic equipment, and in particular to a microcrystalline glass, tempered glass, a preparation method thereof, a housing of an electronic device, a display screen of an electronic device, and an electronic device. Background Art
[0002] Since the advent of smartphones, cover materials have gradually evolved from plastic to glass. Among back panel materials, glass has emerged as the mainstream choice for mid- to high-end phones, standing out from a host of other materials, including plastic, metal, and ceramic, thanks to its superior wear resistance, plasticity, cost-effectiveness, and support for wireless charging. However, glass has a major drawback: poor drop resistance.
[0003] In order to improve the drop resistance of mobile phone glass, the industry has mainly made improvements and optimizations in two aspects. The first is to improve the glass composition, gradually developing from soda-lime silicate glass to high-aluminum silicate glass and the recent super-ceramic glass; the second is to optimize the chemical strengthening process of glass, developing from a one-step method to a two-step method and a multi-step ion exchange process. Among them, super-ceramic glass is microcrystalline glass, which improves the fracture toughness of glass (K IC ) Improve the glass's drop resistance. Summary of the Invention
[0004] The present application provides a microcrystalline glass, tempered glass, a preparation method thereof, a housing of an electronic device, a display screen of an electronic device, and an electronic device, which improves the fracture toughness and drop resistance of the glass, and solves the technical problem of poor drop resistance of glass used as a housing or display screen of an electronic device.
[0005] In order to achieve the above objectives, this application provides the following technical solutions:
[0006] A glass-ceramic is obtained by subjecting a mother glass to a microcrystallization process, wherein the mother glass comprises:
[0007] 50 mol% to 70 mol% SiO2;
[0008] 20 mol% to 30 mol% of Li2O+Na2O+K2O;
[0009] 1 mol% to 15 mol% CaO+SrO+BaO;
[0010] 1 mol% to 5 mol% Al2O3;
[0011] 0.5 mol% to 3 mol% F - ;
[0012] 0.05 mol% to 5 mol% P2O5;
[0013] 0-0.5 mol% Mn2O3;
[0014] 0-0.5 mol% CuO;
[0015] 0-0.5 mol% FeO;
[0016] 0-1 mol% Mn2O3+CuO+FeO;
[0017] Among them, CaO and SrO are not 0 at the same time;
[0018] Li2O and Na2O are not 0 at the same time.
[0019] The present invention performs microcrystallization on the matrix glass of the above composition to precipitate nano-crystal particles to obtain micro-crystal glass. The nano-crystal particles can reduce the concentrated stress at the crack tip, deflect and hinder the expansion of micro-cracks, and thus improve the drop resistance of the glass. Experimental results show that the fracture toughness of the glass provided by the present invention after micro-crystallization is 1.0Mpa·m 1 / 2 The above is more than 20% higher than that of non-microcrystallized glass; the drop height is more than 1000mm, which is more than 30% higher than that of non-microcrystallized glass. At the same time, in this application, the microcrystallization treatment does not affect the light transmittance of the glass. The transmittance of the obtained microcrystallized glass at a wavelength of 400nm to 1000nm is more than 88% (1mm thick), which is not significantly lower than that of non-microcrystallized glass. At the same time, the microcrystallization treatment significantly reduces the transparency of the obtained glass, and it can be used as the non-display area of electronic devices.
[0020] In an exemplary embodiment, the mother glass comprises:
[0021] 55 mol% to 65 mol% SiO2;
[0022] 20 mol% to 30 mol% Li2O;
[0023] 0-5 mol% Na2O;
[0024] 0-5 mol% K2O;
[0025] 1 mol% to 10 mol% CaO;
[0026] 1 mol% to 10 mol% SrO;
[0027] 0-5 mol% BaO;
[0028] 1 mol% to 3 mol% Al2O3;
[0029] 0.5 mol% to 2 mol% F- ;
[0030] 1 mol% to 3 mol% P2O5;
[0031] 0-0.5 mol% Mn2O3;
[0032] 0-0.5 mol% CuO;
[0033] 0-0.5 mol% FeO;
[0034] 0~1mol%Mn2O3+CuO+FeO.
[0035] In another exemplary embodiment, the mother glass comprises:
[0036] 58 mol% to 65 mol% SiO2;
[0037] 23 mol% to 29 mol% Li2O;
[0038] 0-3 mol% Na2O;
[0039] 0-3 mol% K2O;
[0040] 3 mol% to 8 mol% CaO;
[0041] 3 mol% to 8 mol% SrO;
[0042] 1-5 mol% BaO;
[0043] 1 mol% to 2 mol% Al2O3;
[0044] 0.5 mol% to 1.5 mol% F - ;
[0045] 1 mol% to 2 mol% P2O5;
[0046] 0-0.5 mol% Mn2O3;
[0047] 0-0.5 mol% CuO;
[0048] 0-0.5 mol% FeO;
[0049] 0~1mol%Mn2O3+CuO+FeO.
[0050] In the glass-ceramics provided by an exemplary embodiment of the present application, the microcrystalline phase includes one or both of Ca5(PO4)3F and Sr5(PO4)3F and one or both of Li2Si2O5 and Li2SiO3. -The introduction of can promote the formation of a large number of nano-microcrystalline nuclei in the system, and again F - It can also serve as a nucleation center, which greatly increases the number of crystal nuclei. In the process of crystal nuclei growing, they affect each other, thus inhibiting the growth of crystals, making the average particle size small and the crystallinity high. - It can form Ca5(PO4)3F or Sr5(PO4)3F nano-crystal particles with P2O5, Ca and Sr to obtain microcrystalline glass and improve its drop resistance.
[0051] The present application also provides a chemically strengthened glass, which is obtained by subjecting a mother glass to microcrystallization and chemical strengthening treatments, wherein the mother glass comprises:
[0052] 50 mol% to 70 mol% SiO2;
[0053] 20 mol% to 30 mol% of Li2O+Na2O+K2O;
[0054] 1 mol% to 15 mol% CaO+SrO+BaO;
[0055] 1 mol% to 5 mol% Al2O3;
[0056] 0.5 mol% to 3 mol% F - ;
[0057] 0.05 mol% to 5 mol% P2O5;
[0058] 0-0.5 mol% Mn2O3;
[0059] 0-0.5 mol% CuO;
[0060] 0-0.5 mol% FeO;
[0061] 0-1 mol% Mn2O3+CuO+FeO;
[0062] Among them, CaO and SrO are not 0 at the same time;
[0063] Li2O and Na2O are not 0 at the same time.
[0064] In this embodiment, chemical strengthening treatment is performed on glass-ceramics to form a compressive stress layer on the glass surface, further improving properties such as fracture toughness. Experimental results show that after chemical strengthening, the resulting tempered glass can achieve a drop height of over 1300mm and a surface stress of over 450MPa.
[0065] In an exemplary embodiment, the mother glass comprises:
[0066] 55 mol% to 65 mol% SiO2;
[0067] 20 mol% to 30 mol% Li2O;
[0068] 0-5 mol% Na2O;
[0069] 0-5 mol% K2O;
[0070] 1 mol% to 10 mol% CaO;
[0071] 1 mol% to 10 mol% SrO;
[0072] 0-5 mol% BaO;
[0073] 1 mol% to 3 mol% Al2O3;
[0074] 0.5 mol% to 2 mol% F - ;
[0075] 1 mol% to 3 mol% P2O5;
[0076] 0-0.5 mol% Mn2O3;
[0077] 0-0.5 mol% CuO;
[0078] 0-0.5 mol% FeO;
[0079] 0~1mol%Mn2O3+CuO+FeO.
[0080] In another exemplary embodiment, the mother glass comprises:
[0081] 58 mol% to 65 mol% SiO2;
[0082] 23 mol% to 29 mol% Li2O;
[0083] 0-3 mol% Na2O;
[0084] 0-3 mol% K2O;
[0085] 3 mol% to 8 mol% CaO;
[0086] 3 mol% to 8 mol% SrO;
[0087] 1-5 mol% BaO;
[0088] 1 mol% to 2 mol% Al2O3;
[0089] 0.5 mol% to 1.5 mol% F - ;
[0090] 1 mol% to 2 mol% P2O5;
[0091] 0-0.5 mol% Mn2O3;
[0092] 0-0.5 mol% CuO;
[0093] 0-0.5 mol% FeO;
[0094] 0~1mol%Mn2O3+CuO+FeO.
[0095] The glass provided in this application can be used as a cover plate of an electronic device housing or a back plate of an electronic device display screen, so that it has the advantages of glass material such as wear resistance, high cost performance, and support for wireless charging, while also having the characteristics of good drop resistance and anti-drop performance.
[0096] This application also provides methods for preparing the glass-ceramics and chemically strengthened glass described in the above technical solutions. Glass-ceramics can be obtained by subjecting the parent glass to a microcrystallization treatment. In an exemplary embodiment, the microcrystallization treatment is performed at a temperature of 400-800°C for a duration of 30-600 minutes.
[0097] Chemically strengthened glass can be obtained by further subjecting the above-mentioned glass-ceramics to a chemical strengthening treatment. In one exemplary embodiment, the chemical strengthening treatment includes: subjecting the phase-separated glass to ion exchange in a molten potassium salt. In another exemplary embodiment, the chemical strengthening treatment includes: subjecting the phase-separated glass to a first ion exchange in a first molten salt, followed by a second ion exchange in a second molten salt, wherein the first molten salt is a mixed molten salt of potassium nitrate and sodium nitrate, and the second molten salt is potassium nitrate.
[0098] This application provides a housing for an electronic device, comprising the glass-ceramic or chemically strengthened glass described in the above technical solution. For example, the glass-ceramic or chemically strengthened glass can be used as the back panel material of an electronic device, thereby providing the electronic device with the advantages of glass materials, such as aesthetics and high wear resistance, while also improving its drop resistance.
[0099] This application provides a display screen for an electronic device, comprising the glass-ceramic or chemically strengthened glass described in the above technical solution. For example, the glass-ceramic or chemically strengthened glass can be used as a cover material for an electronic device, i.e., as an external screen of the electronic device, thereby improving the electronic device's drop resistance and extending its service life.
[0100] The present application also provides an electronic device, comprising at least one of the shell described in the above technical solution and the display screen described in the above technical solution. The electronic device has the advantages of wear resistance, high cost performance, support for wireless charging, etc., and has the characteristics of good drop resistance and anti-drop performance.
[0101] It should be understood that the description of technical features, technical solutions, beneficial effects or similar language in this application does not imply that all features and advantages can be realized in any single embodiment. On the contrary, it is understood that the description of a feature or beneficial effect means that a specific technical feature, technical solution or beneficial effect is included in at least one embodiment. Therefore, the description of a technical feature, technical solution or beneficial effect in this specification does not necessarily refer to the same embodiment. Furthermore, the technical features, technical solutions and beneficial effects described in the present embodiment can also be combined in any appropriate manner. Those skilled in the art will understand that the embodiment can be implemented without one or more specific technical features, technical solutions or beneficial effects of a specific embodiment. In other embodiments, additional technical features and beneficial effects can also be identified in specific embodiments that do not embody all embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0102] Figure 1 Schematic diagram of the morphology of glass-ceramics;
[0103] Figure 2 TEM image of glass-ceramics;
[0104] Figure 3 Transmittance curves of the glass provided in Example 2-1 and Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0105] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. The terms used in the following embodiments are only for the purpose of describing specific embodiments and are not intended to be limiting of the present application. As used in the specification and appended claims of the present application, the singular expressions "one", "a kind of", "said", "above", "the" and "this" are intended to also include expressions such as "one or more", unless there is a clear contrary indication in the context. It should also be understood that in the embodiments of the present application, "one or more" refers to one, two or more; "and / or" describes the association relationship of associated objects, indicating that three relationships may exist; for example, A and / or B can represent: the existence of A alone, the existence of A and B at the same time, and the existence of B alone, where A and B can be singular or plural. The character " / " generally indicates that the related objects before and after are in an "or" relationship.
[0106] References to "one embodiment" or "some embodiments" in this specification mean that a particular feature, structure, or characteristic described in conjunction with that embodiment is included in one or more embodiments of the present application. Thus, phrases such as "in one embodiment," "in some embodiments," "in other embodiments," and "in yet other embodiments" appearing in various places in this specification do not necessarily refer to the same embodiment, but rather mean "one or more but not all embodiments," unless otherwise specifically emphasized. The terms "including," "comprising," "having," and variations thereof mean "including but not limited to," unless otherwise specifically emphasized.
[0107] The "multiple" involved in the embodiments of the present application means greater than or equal to two. It should be noted that in the description of the embodiments of the present application, the words "first" and "second" are only used for the purpose of distinguishing the description and cannot be understood as indicating or implying relative importance or order.
[0108] In the embodiments of this application, words such as "exemplary" or "for example" are used to indicate examples, illustrations, or descriptions. Any embodiment or design described as "exemplary" or "for example" in the embodiments of this application should not be interpreted as being preferred or advantageous over other embodiments or designs. Rather, the use of words such as "exemplary" or "for example" is intended to present the relevant concepts in a concrete manner.
[0109] In this application, mother glass refers to the glass obtained by mixing, melting, cooling and forming various raw materials. It is the raw material for preparing microcrystalline glass and is used to distinguish it from microcrystalline glass after microcrystallization and strengthened glass after ion exchange. It has no other special meaning.
[0110] In this application, compressive stress is the value obtained by dividing the compressive load applied to a sample during a compression test by the original cross-sectional area of the sample, and is used to characterize the performance of glass.
[0111] In this application, glass formers, also known as glass formers and glass network formers, refer to oxides that can form a glass network structure alone, including but not limited to silicon dioxide, boron trioxide, etc.; network exomers, also known as glass network modifiers or glass adjusters, are oxides that cannot form a network that constitutes glass alone but can change the network, including but not limited to sodium oxide, potassium oxide, magnesium oxide, lithium oxide, barium oxide, etc.; network intermediates, also known as glass network intermediate oxides, refer to oxides whose properties are between those of glass formers and network exomers, including but not limited to aluminum oxide, lead oxide, etc.
[0112] In this application, the back panel is part of the electronic device housing, and may also be referred to as a battery cover or back cover, and is used to protect the battery; the cover is part of the electronic device display screen, and may also be referred to as the outer screen of the display screen, and is used to protect the inner screen with display function in the display screen.
[0113] Glass drop damage is mainly caused by the expansion of existing microcracks in the glass, and crack expansion is related to stress concentration at the crack tip on the material surface. Microcrystalline glass uses nano-scale microcrystalline particles in the glass to reduce the concentrated stress at the crack tip, deflect and hinder the expansion of microcracks, thereby improving the glass's drop resistance.
[0114] Glass-ceramics has a microcrystalline phase, such as Figure 1 As shown, Figure 1 Figure 1 is a schematic diagram of the morphology of glass-ceramics, where 1 is the microcrystalline phase and 2 is the glass phase. The microcrystalline phase can inhibit the spread of cracks, thereby improving the mechanical strength of the glass, such as Young's modulus and fracture toughness. After chemical strengthening, it further improves mechanical properties such as peeling resistance, pressure resistance, and scratch resistance, making glass-ceramics suitable for electronic devices. Currently, the microcrystalline phase of glass-ceramics is generally Li2Si2O5 or Li2SiO3 nanocrystalline particles. Although glass-ceramics with this microcrystalline phase have improved drop resistance compared to non-microcrystallized glass, for example, the drop height can be increased from 600mm to 700mm or even 800mm, its drop resistance still needs to be further improved.
[0115] The glass provided in this application is obtained by microcrystallizing and chemically strengthening the mother glass, and can be used as the back panel or cover panel of a mobile phone, or in electronic devices such as watches and tablets.
[0116] In one embodiment, the components forming the matrix glass include:
[0117] 50 mol% to 70 mol% SiO2;
[0118] 20 mol% to 30 mol% of Li2O+Na2O+K2O;
[0119] 1 mol% to 15 mol% CaO+SrO+BaO;
[0120] 1 mol% to 5 mol% Al2O3;
[0121] 0.5 mol% to 3 mol% F - ;
[0122] 0.05 mol% to 5 mol% P2O5;
[0123] 0-0.5 mol% Mn2O3;
[0124] 0-0.5 mol% CuO;
[0125] 0-0.5 mol% FeO;
[0126] 0-1 mol% Mn2O3+CuO+FeO;
[0127] Wherein, CaO and SrO are not 0 mol% at the same time;
[0128] Li2O and Na2O are not 0 mol% at the same time.
[0129] In this embodiment, SiO2 is used as the main component of the glass. SiO2, as a glass former, imparts excellent structural stability, chemical stability, mechanical properties, and forming properties to the matrix glass. In one embodiment, the SiO2 content is 50 mol% to 70 mol%. In another embodiment, the SiO2 content is 55 mol% to 65 mol%. In another embodiment, the SiO2 content is 58 mol% to 65 mol%.
[0130] In one embodiment, Li2O can react with SiO2 to form Li2Si2O5 or Li2SiO3 nanocrystalline particles, which precipitate from the glass, converting the matrix glass into glass-ceramics. In one embodiment, the Li2O content is 20-30 mol%. In another embodiment, the Li2O content is 23-29 mol%.
[0131] In other embodiments, Li2O can also serve as a network outer layer to reduce the viscosity of the glass melt, thereby promoting rapid melting and clarification of the glass. In one embodiment, the content of Li2O is 0-7 mol%. In another embodiment, the content of Li2O is 1-5 mol%.
[0132] On the one hand, Na2O can reduce the viscosity of glass liquid and serve as a solvent for making glass. On the other hand, it is used for subsequent reaction with K + Ion exchange is performed to generate high compressive stress on the glass surface. In one embodiment, the content of Na2O is 0-5 mol%. In another embodiment, the content of Na2O is 0-3 mol%.
[0133] K2O can improve the melting and clarification of glass. In one embodiment, the content of K2O is 0-5 mol%; in another embodiment, the content of K2O is 0 mol%-3 mol%.
[0134] In one embodiment, the total content of Li2O+Na2O+K2O is 20 mol% to 30 mol%. In order to smoothly carry out the subsequent chemical strengthening, the contents of Li2O+Na2O are not both 0.
[0135] Al2O3, as a network intermediate, can improve the peeling stability and mechanical properties of the glass. In one embodiment, the Al2O3 content is 1 mol% to 5 mol%. In another embodiment, the Al2O3 content is 1 mol% to 3 mol%. In another embodiment, the Al2O3 content is 1 mol% to 2 mol%.
[0136] CaO, SrO and BaO as the external components of the glass network can reduce the melting temperature of the glass and facilitate clarification. At the same time, Ca and Sr can react with P2O5 and F - Forming Ca5(PO4)3F or Sr5(PO4)3F nanocrystalline particles improves the drop resistance of the microcrystalline glass. In one embodiment, the content of CaO+SrO+BaO is 1 mol% to 15 mol%, and the contents of CaO and SrO are different and are 0. In one embodiment, the content of CaO is 1 to 10 mol%. In one embodiment, the content of SrO is 1 to 10 mol%. In one embodiment, the content of BaO is 0 to 5 mol%. In one embodiment, the content of CaO is 3 to 8 mol%. In one embodiment, the content of SrO is 3 to 8 mol%. In one embodiment, the content of BaO is 1 to 5 mol%.
[0137] This application introduces F into glass - , F - The introduction of can promote the formation of a large number of nano-microcrystalline nuclei in the system, and again F - It can also serve as a nucleation center, which greatly increases the number of crystal nuclei. In the process of crystal nuclei growing, they affect each other, thus inhibiting the growth of crystals, making the average particle size small and the crystallinity high. - It can form Ca5(PO4)3F or Sr5(PO4)3F nanocrystalline particles with P2O5, Ca and Sr, thereby obtaining microcrystalline glass and improving its drop resistance. In one embodiment, F - The content of F is 0.5 mol% to 3 mol%. In one embodiment, F - The content of F is 0.5 mol% to 2 mol%. In one embodiment, F - The content is 0.5 mol% to 1.5 mol%.
[0138] As a glass former, P2O5 forms a layered network structure, which is beneficial to the diffusion of ions in the glass and promotes chemical strengthening. It can also react with F -, Ca and Sr form Ca5(PO4)3F or Sr5(PO4)3F nanocrystalline particles. In one embodiment, the content of P2O5 is 0.05mol% to 5mol%. In one embodiment, the content of P2O5 is 1mol% to 3mol%. In one embodiment, the content of P2O5 is 1mol% to 2mol%.
[0139] Mn2O3 can be used as a colorant to change the color of glass, such as changing the glass to purple. In one embodiment, the content of Mn2O3 is 0-0.5 mol%.
[0140] CuO, as a colorant, can change the color of glass, such as changing the glass to blue, or adjust the color of glass with other colorants, such as MnO2, Nd2O3, etc. In one embodiment, the content of CuO is 0-0.5 mol%.
[0141] FeO can be used as a colorant to change the color of glass, such as changing the glass to blue. In one embodiment, the content of FeO is 0-0.5 mol%.
[0142] In one embodiment, the content of Mn2O3+CuO+FeO is 0-1 mol%. In one embodiment, the content of Mn2O3+CuO+FeO is 0-0.5 mol%.
[0143] In one embodiment, the components forming the matrix glass include:
[0144] 55 mol% to 65 mol% SiO2;
[0145] 20 mol% to 30 mol% Li2O;
[0146] 0-5 mol% Na2O;
[0147] 0-5 mol% K2O;
[0148] 20 mol% to 30 mol% of Li2O+Na2O+K2O;
[0149] 1 mol% to 10 mol% CaO;
[0150] 1 mol% to 10 mol% SrO;
[0151] 0-5 mol% BaO;
[0152] 1 mol% to 15 mol% CaO+SrO+BaO;
[0153] 1 mol% to 3 mol% Al2O3;
[0154] 0.5 mol% to 2 mol% F - ;
[0155] 1 mol% to 3 mol% P2O5;
[0156] 0-0.5 mol% Mn2O3;
[0157] 0-0.5 mol% CuO;
[0158] 0-0.5 mol% FeO;
[0159] 0~1mol%Mn2O3+CuO+FeO.
[0160] After the mother glass meeting the above composition undergoes microcrystallization and chemical strengthening treatment, its drop resistance is further improved.
[0161] In one embodiment, the components forming the matrix glass include:
[0162] 58 mol% to 65 mol% SiO2;
[0163] 23 mol% to 29 mol% Li2O;
[0164] 0-3 mol% Na2O;
[0165] 0-3 mol% K2O;
[0166] 20 mol% to 30 mol% of Li2O+Na2O+K2O;
[0167] 3 mol% to 8 mol% CaO;
[0168] 3 mol% to 8 mol% SrO;
[0169] 1-5 mol% BaO;
[0170] 1 mol% to 15 mol% CaO+SrO+BaO;
[0171] 1 mol% to 2 mol% Al2O3;
[0172] 0.5 mol% to 1.5 mol% F - ;
[0173] 1 mol% to 2 mol% P2O5;
[0174] 0-0.5 mol% Mn2O3;
[0175] 0-0.5 mol% CuO;
[0176] 0-0.5 mol% FeO;
[0177] 0~1mol%Mn2O3+CuO+FeO.
[0178] After the matrix glass meeting the above composition undergoes microcrystallization treatment and chemical strengthening treatment, especially chemical strengthening treatment, its drop resistance performance is more significantly improved.
[0179] In one embodiment, the mother glass is transparent glass, and its transmittance at a wavelength of 400 nm to 1000 nm is above 90% (1 mm thick).
[0180] The present application does not particularly limit the manufacturing method of the mother glass. For example, the mother glass can be obtained by uniformly mixing and stirring the raw materials, heating them until they are fully melted, and cooling them to form them. In one embodiment, the melting temperature is 1400-1600°C, and the melting and holding time is 50-120 minutes. It is understood that during the preparation of the mother glass, homogenization can be achieved by degassing, stirring, and other methods during the melting process. Specific methods of cooling and forming include but are not limited to forming into plate-shaped glass by float method, down-draw method, pressing method, or flattening method, or forming into block-shaped glass by casting.
[0181] The raw materials used in preparing the matrix glass of the present invention may be oxides, composite oxides, carbonates, hydroxides, and hydrates thereof. For example, oxides may include silica sand (SiO2), aluminum oxide (Al2O3), copper oxide (CuO), etc.; composite oxides may include sodium metaphosphate (NaPO3), aluminum metaphosphate (Al(PO3)3), aluminum fluoride (AlF3), etc.; carbonates may include sodium carbonate, potassium carbonate, calcium carbonate, strontium carbonate, etc.; hydroxides may include aluminum hydroxide, etc.; and hydrates may include phosphoric acid, etc.
[0182] After obtaining the mother glass, it is subjected to a microcrystallization treatment. During the treatment process, the corresponding components can form nano-microcrystalline particles, which are precipitated from the glass phase to obtain microcrystalline glass. The present application performs a heat treatment on the mother glass to make it microcrystallized. During the heat treatment process, the nano-microcrystalline particles undergo two processes: nucleation and growth. The type, size and content of the precipitated nano-microcrystalline particles can be adjusted by controlling different nucleation and growth times and temperatures. The present invention has no special restrictions on this. In one embodiment, the heat treatment temperature is 400-800°C and the time is 30-600min. In one embodiment, the heat treatment temperature is 450-750°C and the time is 40-400min. In one embodiment, the heat treatment temperature is 500-650°C and the time is 50-350min.
[0183] After the mother glass provided in the embodiment of the present application is microcrystallized, the precipitated nanocrystalline particles include at least one of the Ca5(PO4)3F and Sr5(PO4)3F crystal phases, and may also include one or more of Li2Si2O5 and Li2SiO3. The precipitated nanocrystalline particles are generally spherical nanocrystalline particles with a size of generally 1nm to 300nm, see Figure 2 As shown, Figure 2 TEM image of the glass-ceramic provided in Example 2-1 of the present invention. In one embodiment, the average particle size of the nano-crystal particles is 1 to 100 nm, and the nano-crystal particles account for more than 50% of the entire glass-ceramic. In one embodiment, the average particle size of the nano-crystal particles is 1 to 50 nm, and the nano-crystal particles account for more than 80% of the entire glass-ceramic.
[0184] After microcrystallization, the microcrystalline nanoparticles precipitated from the glass phase can effectively hinder the propagation of microcracks in the glass, improve the mechanical strength of the glass, such as fracture toughness, and thus improve the drop resistance of the glass. Experimental results show that the fracture toughness of the glass provided by the present invention after microcrystallization is 1.0Mpa·m 1 / 2 The drop height is above 1000cm, which is an increase of more than 30%.
[0185] At the same time, in this application, the microcrystallization treatment does not affect the transmittance of the glass. The obtained microcrystal glass is still transparent glass. The transmittance at a wavelength of 400nm to 1000nm is above 88%, preferably above 90% (1mm thick), and the transmittance does not decrease significantly. Figure 3 , Figure 3 Transmittance curves of the glass-ceramics provided in Example 2-1 and Comparative Example 2 of the present invention.
[0186] In this application, due to the high temperature and long time of the microcrystallization treatment, the content of nano-microcrystalline particles in the glass is relatively high, and the transparency of the glass material decreases significantly, so it can be used as a non-display area in the field of electronic products.
[0187] The microcrystalline glass obtained by the present invention can be used as a cover plate or back plate material for electronic devices, such as a mobile phone 2D glass back plate, 3D glass back plate, 2.5D glass back plate or glass cover plate.
[0188] In one embodiment, after obtaining the glass-ceramics, it can also be chemically strengthened to further improve the glass's fracture toughness and other properties. Specifically, after obtaining the glass-ceramics, the glass-ceramics are processed into the desired shape according to their intended use and then subjected to chemical strengthening treatment or directly subjected to chemical strengthening treatment. For example, the glass-ceramics can be cut, CNC-shaped, and polished to obtain a flat mobile phone back panel; or the glass-ceramics can be cut, CNC-shaped, 3D-bent, and polished to obtain a 3D mobile phone back panel. 3D bending involves hot-pressing the CNC-finished glass raw material using a hot bending machine in conjunction with a forming mold, bending the glass into the desired shape, i.e., 3D glass shaping.
[0189] After obtaining the desired shape of the glass-ceramics, it is chemically strengthened to form a compressive stress layer on the glass surface, thereby increasing the strength of the glass. The chemical strengthening treatment can be performed by primary ion exchange or secondary ion exchange to form an ion exchange layer, and this application does not specifically limit this.
[0190] Specifically, the primary ion exchange process includes exchanging the glass-ceramics with molten potassium salt. In one embodiment, the molten potassium salt may be potassium nitrate. The ion exchange process is performed at a temperature of 400°C to 500°C for 4 to 7 hours. In one embodiment, the ion exchange process is performed at a temperature of 450°C for 6 hours.
[0191] The secondary ion exchange includes: subjecting the glass-ceramics to a first ion exchange in a first molten salt, and then subjecting it to a second ion exchange in a second molten salt. In one embodiment, the first molten salt is a mixed molten salt of potassium nitrate and sodium nitrate, the temperature of the first ion exchange is 400-600°C, and the time is 80-400 minutes; the second molten salt is potassium nitrate, the temperature of the second ion exchange is 400-500°C, and the time is 20-180 minutes. In one embodiment, the first molten salt is a mixed molten salt of potassium nitrate and sodium nitrate, the temperature of the first ion exchange is 400-500°C, and the time is 100-300 minutes; the second molten salt is potassium nitrate, the temperature of the second ion exchange is 400-500°C, and the time is 30-150 minutes.
[0192] After chemical strengthening treatment, the drop height of the obtained tempered glass can reach more than 1300mm; the surface stress can reach more than 450MPa.
[0193] After the chemical strengthening treatment, the glass may be subjected to subsequent treatments such as pad printing and coating (AF) according to its intended use, and this application does not impose any particular restrictions thereon.
[0194] The glass provided in this application can be used as a cover plate of an electronic device housing or a back plate of an electronic device display screen, so that it has the advantages of glass material such as wear resistance, high cost performance, and support for wireless charging, while also having the characteristics of good drop resistance and anti-drop performance.
[0195] The electronic device mentioned in this application can be any device with communication and storage functions, such as smartphones, cellular phones, cordless phones, Session Initiation Protocol (SIP) phones, tablet computers, personal digital assistants (PADs), laptop computers, digital cameras, e-book readers, portable multimedia players, handheld devices with wireless communication functions, computing devices or other processing devices connected to wireless modems, vehicle-mounted devices, wearable devices, 5G terminal devices, etc. The embodiments of this application are not limited to this.
[0196] The glass-ceramics, tempered glass, preparation methods thereof, housings of electronic devices, display screens of electronic devices, and electronic devices provided by the present application are described in detail below with reference to the embodiments.
[0197] The glass was prepared according to the formula and process parameters shown in Table 1. The specific method is as follows:
[0198] SiO2, Li2CO3, Na2CO3, K2CO3, CaCO3, SrCO3, BaCO3, AlF3, Al(PO3)3, Al3O2 and other raw materials are placed in a mortar and fully stirred to obtain a batch material, and then the batch material is transferred to a high-temperature furnace at 1400-1600°C and kept warm for 1.5-2 hours to fully melt the batch material, and then the molten batch material is cooled and formed to obtain a transparent matrix glass material;
[0199] The mother glass is placed in a resistance furnace at 400-800° C. for heat treatment for 30-600 minutes, so that the mother glass undergoes a nanocrystal nucleation and growth process at high temperature to obtain nano-crystal glass;
[0200] After cutting, the nano-crystalline glass is subjected to a two-step ion exchange to obtain chemically strengthened glass. The ion exchange specifically includes: soaking in a sodium potassium salt (KNO3+NaNO3) solution at a temperature of about 450°C for 200 minutes and then taking it out; then soaking in a molten potassium salt (KNO3) solution at a temperature of about 450°C for 100 minutes and then taking it out for cleaning.
[0201] The glass was subjected to performance testing, and the results are shown in Table 1. The testing method is as follows:
[0202] The fracture toughness test refers to the national standard GB / T 37900-2019 (Test method for hardness and fracture toughness of ultra-thin glass), and the sample is tested by the small load Vickers hardness indentation method. It should be noted that when the fracture toughness of the samples in each embodiment is tested after chemical strengthening, each sample is pressurized with a pressure of 10Kgf (the maximum pressure supported by the detection equipment), and no cracks appear. Therefore, the fracture toughness value after chemical strengthening is not counted. It can be seen that the fracture toughness of the sample after chemical strengthening is much higher than that before chemical strengthening.
[0203] The glass surface stress and ion exchange layer depth were measured using a glass surface stress meter SLP-2000. During the test, the refractive index of the sample was set to 1.47 and the optical elastic constant was set to 65 nm / cm / MPa.
[0204] The drop ball test refers to the national standard GB / T 39814-2021 (Test method for impact strength of ultra-thin glass). The specimen is processed into 150mm×75mm×0.55mm, and after polishing both surfaces, a 32g steel ball is dropped from a specified height. The maximum drop ball test height that the sample can withstand without breaking is determined.
[0205] Table 1: Formulations, process parameters, and performance test results of the glasses prepared in the examples and comparative examples of the present application
[0206]
[0207] Table 1 (continued)
[0208]
[0209] In Comparative Example 4 and Examples 4-1 and 4-2, since a small amount of CuO is added in the glass composition design, the color of the sample after melting is blue.
[0210] As can be seen from Table 1, the fracture toughness and ball drop height of the glass provided by the present invention are significantly improved after microcrystallization treatment, thereby improving its drop resistance and anti-drop performance as a cover or back panel of an electronic device, especially a mobile phone. Furthermore, after chemical strengthening treatment, the fracture toughness and ball drop height of the glass are further improved, and its drop resistance and anti-drop performance are further improved. When used as a cover or back panel of an electronic device, it can increase the service life of the electronic device.
[0211] The above is only a specific embodiment of the present application, but the scope of protection of this application is not limited to this. Any changes or substitutions within the technical scope disclosed in this application should be included in the scope of protection of this application. Therefore, the scope of protection of this application should be based on the scope of protection of the claims.
Claims
1. A glass-ceramic for electronic equipment, characterized in that: It is composed of the following components: 50 mol% to 70 mol% SiO2; 20 mol% to 30 mol% Li2O+Na2O+K2O; 1 mol% to 15 mol% CaO+SrO+BaO; 1 mol% to 5 mol% Al2O3; 0.5 mol% to 3 mol% F - ; 0.05 mol% to 5 mol% P2O5; 0-0.5 mol% Mn2O3; 0-0.5 mol% CuO; 0-0.5 mol% FeO; 0-1 mol% Mn2O3+CuO+FeO; Wherein, CaO and SrO are not 0 mol% at the same time; Li2O and Na2O are not 0mol% at the same time; The transmittance of the microcrystalline glass at a wavelength of 400nm to 1000nm is above 88%; The drop height of the glass-ceramics is above 1000 mm; The glass-ceramics is transparent glass.
2. The glass-ceramic according to claim 1, characterized in that: It is composed of the following components: 55 mol% to 65 mol% SiO2; 20 mol% to 30 mol% Li2O; 0-5 mol% Na2O; 0-5 mol% K2O; 1 mol% to 10 mol% CaO; 1 mol% to 10 mol% SrO; 0-5 mol% BaO; 1 mol% to 3 mol% Al2O3; 0.5 mol% to 2 mol% F - ; 1 mol% to 3 mol% P2O5; 0-0.5 mol% Mn2O3; 0-0.5 mol% CuO; 0-0.5 mol% FeO; 0~1mol%Mn2O3+CuO+FeO.
3. The glass-ceramic according to claim 2, characterized in that: It is composed of the following components: 58 mol% to 65 mol% SiO2; 23 mol% to 29 mol% Li2O; 0-3 mol% Na2O; 0-3 mol% K2O; 3 mol% to 8 mol% CaO; 3 mol% to 8 mol% SrO; 1 to 5 mol% BaO; 1 mol% to 2 mol% Al2O3; 0.5 mol% to 1.5 mol% F - ; 1 mol% to 2 mol% P2O5; 0-0.5 mol% Mn2O3; 0-0.5 mol% CuO; 0-0.5 mol% FeO; 0~1mol%Mn2O3+CuO+FeO.
4. The glass-ceramics according to any one of claims 1 to 3, characterized in that: The microcrystalline phase of the microcrystalline glass includes one or two of Ca5(PO4)3F and Sr5(PO4)3F and one or two of Li2Si2O5 and Li2SiO3.
5. The glass-ceramic according to claim 4, characterized in that: The fracture toughness of the glass-ceramics is 1.0 Mpa·m 1 / 2 above.
6. The glass-ceramic according to claim 1, characterized in that: The method for preparing the microcrystalline glass comprises the following steps: The mother glass is microcrystallized to obtain microcrystalline glass.
7. The glass-ceramics according to claim 6, characterized in that: The temperature of the microcrystallization treatment is 400-800° C., and the time is 30-600 min.
8. A chemically strengthened glass, characterized in that: The microcrystalline glass according to any one of claims 1 to 7 is obtained by chemically strengthening treatment.
9. The chemically strengthened glass according to claim 8, wherein: The chemically strengthened glass has a compressive stress layer on its surface.
10. The chemically strengthened glass according to claim 8, wherein: The chemically strengthened glass has an ion exchange layer on its surface.
11. The chemically strengthened glass according to any one of claims 8 to 10, characterized in that: The surface stress of the chemically strengthened glass is 450 MPa or more.
12. The chemically strengthened glass according to claim 11, wherein: The ball drop height of the chemically strengthened glass is 1300 mm or more.
13. The chemically strengthened glass according to claim 8, characterized in that: The chemical strengthening treatment specifically includes: Ion exchange of glass-ceramics in molten potassium salt; Or, include: The microcrystalline glass is subjected to a first ion exchange in a first molten salt, and then subjected to a second ion exchange in a second molten salt, wherein the first molten salt is a mixed molten salt of potassium nitrate and sodium nitrate, and the second molten salt is potassium nitrate.
14. A glass product, characterized in that: The glass product is made of the glass-ceramics according to any one of claims 1 to 7 or the chemically strengthened glass according to any one of claims 8 to 13.
15. The glass product according to claim 14, characterized in that The glass product is a glass cover plate, and the glass cover plate is used to cover a screen or a housing of an electronic device.
16. An electronic device comprising the glass product according to claim 14 or 15.
